Subaltern Resistance in the 1965 Novel by Kopong Bunga Lamawuran: Gayatri Spivak's Postcolonial Perspective - Nurul Khaeriyah, Husnaeni; Idawati; Aslan Abidin (Universitas Cokroaminoto Palopo, 2026)
This study discusses how the resistance of the subaltern group is depicted in the 1965 novel by Kopong Bunga Lamawuran using the postcolonial framework of Gayatri Spivak. The main focus of this study is the problem of the marginalization of subaltern voices in the dominant historical narrative as well as the way literature records and conveys these forms of resistance. The purpose of this study is to describe the various resistance of the subaltern as well as to examine the way the text constructs the story, both in providing space and limiting the possibility of the subaltern to speak. This study uses a qualitative approach with an interpretive descriptive design through an in-depth reading of the novel, with data in the form of narratives, dialogues, and relevant storytelling patterns. The results of the study show that the subaltern resistance in the 1965 novel does not always appear directly or openly, but emerges through daily actions, mutual solidarity, efforts to negotiate meaning, and symbols of resistance that take place in the political, economic, social, cultural, knowledge, discourse, and social structures realms. These findings confirm that the subaltern is not a passive party, but continues to try to survive and resist in limitations, while showing literature as an alternative space to present knowledge outside the official narrative of the state.